2012
DOI: 10.1002/anie.201107919
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Uncaging and Bioluminescence Imaging by Using Photocaged Upconversion Nanoparticles

Abstract: Trading up: A bioimaging system that is based on caged D‐luciferin/upconversion nanoparticle conjugate has been developed. The nanoparticles upconvert near‐infrared light into UV light, which triggers the photorelease of D‐luciferin (see scheme) and leads to enhanced fluorescence and bioluminescence signals in vitro and in vivo. The use of near‐infrared light enables deep penetration into tissue in vivo with minimum cellular damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
286
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(289 citation statements)
references
References 92 publications
2
286
0
1
Order By: Relevance
“…In 2010 Carling et al [118] chromophore absorbs only in the UV (λ max = 282 nm), so it is light from the 1 D 2 ⇒ 3 H 6 emission of Tm 3+ at 290 nm that is necessary to trigger this photoreaction, hence the relatively high laser intensity needed. In a more directly biological application Yang et al [119] prepared NaYF 4 :Yb/Tm(20/0.2%)@NaYF 4 core : shell UCNPs (approx. 50 nm) coated with a thiolated SiO 2 layer which was conjugated to D-luciferin caged with a 1-(2-nitrophenyl)ethyl group.…”
Section: Uncaging Using Upconversion Nanoparticles (A) Introduction Tmentioning
confidence: 99%
“…In 2010 Carling et al [118] chromophore absorbs only in the UV (λ max = 282 nm), so it is light from the 1 D 2 ⇒ 3 H 6 emission of Tm 3+ at 290 nm that is necessary to trigger this photoreaction, hence the relatively high laser intensity needed. In a more directly biological application Yang et al [119] prepared NaYF 4 :Yb/Tm(20/0.2%)@NaYF 4 core : shell UCNPs (approx. 50 nm) coated with a thiolated SiO 2 layer which was conjugated to D-luciferin caged with a 1-(2-nitrophenyl)ethyl group.…”
Section: Uncaging Using Upconversion Nanoparticles (A) Introduction Tmentioning
confidence: 99%
“…In addition to photodynamic therapy, UCNPs have been used as energy donors in other photo-responsive drug release systems. 54 Liu and coworkers have reported the first in vivo demonstration of UCNP based photodynamic therapy. 55 UCNPs were synthesized by NaYF4 nanocrystals followed by PEG coating.…”
Section: Up Conversion Nanoparticlesmentioning
confidence: 99%
“…This frequency upconversion moves low energy light to higher energy light. Yang et al [52] demonstrated this concept by using caged D-luciferin [53]. They attached caged D-luciferin on the surface of the UCNPs (Tm/Tb co-doped NaYF4).…”
Section: Drug Release Through the Nir Up Conversion Systemsmentioning
confidence: 99%